Milk Consumption and Its Association with Dental Caries: Gender-Specific Insights from the Korea National Health and Nutrition Examination Survey (2013–2015) - Min, Eun Jeong; Park, EunKyung; Park, Jun-Beom (Medicina (Kaunas, Lithuania), 2024)
Background and Objectives: This study aims to bridge these gaps by utilizing data from the Korea National Health and Nutrition Examination Survey (2013–2015), examining the nuanced associations between milk consumption’s quantity, frequency, and type and the prevalence of dental caries. Materials and Methods: Utilizing data from the Korea National Health and Nutrition Examination Survey (2013–2015), this study explores the association between milk consumption and the prevalence of dental caries in a sample of 4843 subjects (weighted n = 15,581), including 2856 males and 1987 females; weighted sample sizes were 6656 and 8925 for men and women, respectively. The prevalence of dental caries was assessed by evaluating the number of decayed, filled, and missing teeth. Results: The analysis demonstrated a significant positive association between increased milk consumption and the risk of developing dental caries, with an overall odds ratio of 1.653 (95% CI: 1.153–2.370, p < 0.05). The association was more pronounced in females, exhibiting an odds ratio of 1.865 (95% CI: 1.157–3.006, p < 0.05), and age was identified as a significant variable, particularly among participants aged 50 and above. In contrast, the relationship among the male group, though positive (odds ratio: 1.613, 95% CI: 0.991–2.625), was not statistically significant (p = 0.054). Conclusion: These findings suggest that milk consumption may be a potential risk indicator for dental caries, particularly among women, emphasizing the need for targeted dietary recommendations in dental health practices.